The Impact of Innovation Factors on Repurchase Intention: Enhancing the Competitiveness of Indonesian Handicrafts - Wahyuni, Sri; Astuti, Rifelly Dewi (Politeknik Negeri Bandung, 2025)
Traditional handicrafts need to innovate to be able to compete with mass-produced machine-made products that are usually cheaper and easily scalable. The key challenge in handicraft innovation is balancing authenticity and cultural value while adapting to modern consumer preferences without losing the traditional identity that defines these crafts. This study examines the impact of innovation factors—authenticity, packaging, product, and process innovation—on consumers' repurchase intentions for traditional Indonesian handicrafts. A quantitative approach was used, surveying 386 Indonesian respondents aged 18 and above who had purchased handicrafts in the past year. Data were analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that product and process innovations positively affect repurchase intentions, while authenticity and packaging had no significant impact. This research contributes to consumer behavior and innovation literature in the cultural and creative industries and provides insights for enhancing the global competitiveness of Indonesian handicrafts.